Quantitative characterization of the 3D self-organization of PDAC tumor spheroids reveals cell type and matrix dependence through advanced microscopy analysis - Soraya Hernández-Hatibi; Carlos Borau; Neus Martínez-Bosch; Pilar Navarro; José Manuel García-Aznar; Pedro Enrique Guerrero (APL Bioengineering)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by an abundant tumor-associated stroma composed from pancreatic stellate cells, which play a critical role in tumor progression. Developing accurate in vitro models requires understanding the complex interactions between tumor cells and their microenvironment. In this study, we present a quantitative imaging-based characterization of the three dimensional (3D) self-organization of PDAC tumour spheroids using a microfluidic platform that mimics key aspects of the tumor microenvironment. Our model incorporates collagen type I hydrogels to recreate the extracellular matrix, activated human pancreatic stellate cells (HPSCs), and various tumor cell types. Advanced imaging techniques, including Lattice Lightsheet Microscopy, allowed us to analyze the 3D growth and spatial organization of the spheroids, revealing intricate biomechanical interactions. Our results indicate that alterations in matrix properties—such as stiffness, pore size, and hydraulic permeability—due to variations in collagen concentration significantly influence the growth patterns and organization of PDAC spheroids, depending on tumor subtype and epithelial–mesenchymal phenotype. Higher collagen concentrations promoted larger spheroids in epithelial-like cell lines, while mesenchymal-type cells required increased collagen for self-organization into smaller spheroids. Furthermore, coculture with HPSCs affected spheroid formation distinctly based on each PDAC cell line's genetic and phenotypic traits. HPSCs had opposing effects on epithelial-like cell lines: one cell line exhibited enhanced spheroid growth, while another showed inhibited formation, whereas mesenchymal-like spheroids showed minimal impact. These results provide insights into tumor–stroma interactions, emphasizing the importance of the cell-specific and matrix-dependent factors for advancing our understanding of PDAC progression and informing future therapeutic strategies.